(untitled) (Research, Society and Development, 2020)
In the need to seek alternative feedstuffs that aim to reduce costs in broiler rations and the reuse of hatchery waste. It was aimed in this work to evaluate the digestibility and energetic value of dehydrated egg powder for broiler chicks. Three hundred male COBB broilers were used, the experimental design was completely randomized, consisting of two treatments, consisting of five replicates with three broilers in each replicate. Being, treatment A control, reference. And treatment B control, reference with 15% dehydrated egg powder. To perform the analyzes, the total excreta collection method was used. In the evaluations it was found 7.010Kcal / kg of metabolizable energy and digestibility coefficient of crude protein and dry matter of 86.81% and 72.17%, respectively. This data can be included in feedstuffs compositional nutrition tables for broiler feed. It can be concluded that dehydrated whole egg powder can be properly used in broiler feed because it has high energy value and good digestibility, thus following the nutritional parameters described above.